Improving Students' Social Skills Through Cooperative Learning: The Effectiveness of the Teams Games Tournament (TGT) Model - Wulandari, Tarisya Ayuni; Rosdiana, Laily (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Improving Students' Social Skills Through Cooperative Learning: The Effectiveness of the Teams Games Tournament (TGT) Model. This research aims to describe the improvement in students' social skills after carrying out the learning process by implementing the Teams Games Tournament (TGT) type cooperative model on vibration and wave material. The type of research used is a pre-experimental design with a one-shot case Study design. In this research, the subjects used were students in class VIII of one of the State Middle Schools in Sidoarjo. The indicators used in this research are being able to socialize with other people, being able to interact confidently, showing concern, reporting things accurately, completing tasks, avoiding bad behavior, respecting other people's opinions, controlling emotions, and being friendly. The results of the research show that all indicators have experienced a significant increase in the average social skills of students being well-trained as indicated by an increase in the percentage of students' skills at each meeting. At meetings I, II, and III respectively, the percentage increase was 52%, 71%, and 93%. Based on this, it can be concluded that Teams Games Tournament (TGT) type cooperative learning can be used to train students' social skills which is one aspect of cognitive development in vibration and wave material.